Implementation of Higher Education MBKM Program Policies - Mures Walef, Sri; Nikmatulaili, Nikmatulaili; Gustituati, Nurhizrah; Marsidin, Sufyarma (Universitas Negeri Padang, 2023)
Merdeka Learning Merdeka Campus (MBKM) is an independent and versatile higher education learning program designed to create creative, non-restrictive learning that meets students' needs. This study aims to determine the extent of the impact and perceptions of the implementation of Independent Learning Campus Merdeka (MBKM) for all students in tertiary institutions. This study uses a descriptive quantitative approach to the survey method. The population of this study was 215 students consisting of five study programs. The sample of this research is 54 respondents. Data was collected through a questionnaire. Data analysis techniques started from data collection and then analyzed using descriptive analysis. The results of the study showed that the STKIP Abdi Pendidikan Foundation students gave a positive response to the Merdeka Learning Campus Merdeka (MBKM) program, especially in teaching campus programs and student exchangesKeywords: policy, Independent Learning Campus Merdeka (MBKM)